Implementation of audio visual learning media on the narrative writing skills of class IV at elementary school - Wachidah, Kemil; Rahmawati, Ida (Universitas Kanjuruhan Malang, 2025)
This study aims to examine the effect of the implementation of audio-visual learning media on the ability to write narratives of grade IV students at Bligo State Elementary School. The method used is quantitative with a pre-experimental research design of One Group Pretest-Posttest Design type. The sample of this study was all fourth grade students as many as 28 students. The instrument used was a narrative writing test based on six assessment indicators. The results showed that the average posttest score increased compared to the pretest, with the t-test results showing a significance of 0.000 (<0.05) and an eta squared value of 0.991 which showed a very strong influence. Thus, it can be concluded that the use of audio-visual learning media is effective in improving students' narrative writing skills. The use of this media can be used as an alternative to create a more interesting and interactive learning atmosphere.